تطبيق التحليل العاملي في دراسة أهم العوامل الاقتصاديّة المؤثّرة في تغيّر عدد المشتغلين خلال الفترة 2000-2009 في سورية - الرّفاعي, عبد الهادي; اسماعيل, عصام; حبيب, غدير (Latakia University Journal - Economic and Legal Sciences Series, 2013)
إنّ الهدف الرّئيسي لهذا البحث هو تطبيق التحليل العاملي في دراسة أهم العوامل الاقتصاديّة التي تؤثّر في عدد المشتغلين خلال الفترة 2000-2009 في سورية. بغية اقتراح إطار ممنهج لتركيبة متكاملة تشكّل نظام نموذج التحليل العاملي, الذي يمكن استخدامه بوصفه أداة دعم القرار في عمليّة تحليل سنوات التشغيل في سورية ومساعدة متخذ القرار في تحديد السّنوات التي تعاني من مشاكل حقيقيّة. إنّ عيّنة الدّراسة تحتوي على 17 متغيّر اقتصادي موزّعة خلال سنوات الدّراسة التي هي 10 سنوات خلال الفترة 2000-2009, تمّ استخدام تقنيّة التحليل المتعدّد المتغيّرات الذي يرتكز على (تحليل المركب الأساسي), بهدف استكشاف الخصائص الأساسيّة للسنوات من خلال المتغيّرات الاقتصاديّة المدروسة. وتمّ تقدير نماذج (التحليل التمايزي) بالاعتماد على تلك الخصائص المميّزة لتركيب النموذج FAMS. إنّ أهميّة نظام نموذج التحليل العاملي تأتي من خلال استخدامه في عمليّة تقسيم سنوات الدّراسة إلى مجموعتين, المجموعة الأولى وهي مجموعة سنوات التشغيل, والمجموعة الثّانيّة هي مجموعة سنوات انخفاض التشغيل, الأمر الذي يساعد في تحديد سياسة التشغيل الأفضل والتي تساعد في الحدّ من البطالة. كان من أهمّ نتائج الدراسة أنّه في حال أمكن تطبيق النموذج المقترح FAMS, خلال السنوات المعتمدة للدراسة, فإنّه من الممكن في هذه الحالة تحديد نقاط الضعف بحسب السنوات التي كان فيها عدد مشتغلين أقل من المتوسط العام المحسوب خلال الفترة.The objective of this research is applying Factor Analysis for Studying the most important economic factors affecting the number of employees within period 2000 till 2009 in Syria, to propose a methodological framework for constructing the integrated factor analysis model system (FAMS) that can be used as a decision support tool in employment year examination and supervision process for detection of years, which are experiencing serious problems. Sample and variable set of the study contains 17 economic variables. Study years (10 years during the period 2000–2009) and their economic variables. Well known multivariate statistical technique (principal component analysis), was used to explore the basic economic characteristics of the theses years, and discriminant models were estimated based on these characteristics to construct FAMS. The importance of factor analysis model system in employment year examination was evaluated with respect to defining the non-employment years for deciding the most important employment policy for reducing unemployment rates in future. Results of the study show that, if FAMS was effectively employed within studied years, It is possible in this case to identify weaknesses, according to the years that have the number of employees is less than the overall average calculated over the period.